2016
DOI: 10.1089/cap.2015.0175
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline as Adjunctive Treatment to Risperidone in Children with Autistic Disorder: A Randomized, Double-Blind Placebo-Controlled Trial

Abstract: Minocycline seems to be a safe and effective adjuvant in management of patients with autistic disorder. Future studies with larger sample sizes, longer follow-ups, and inflammatory cytokine measurements are warranted to confirm these findings and provide insight into minocycline mechanism of action in autistic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 61 publications
0
23
0
1
Order By: Relevance
“…A small pilot trial (n=10) with minocycline up to six months showed only minimal improvement, and neither yielded any significant behavioral improvement in ASD nor showed any observable changes in key inflammatory cytokines, such as IL-1β, IL-6, TNF-α, or MMP 43). More lately, however, minocycline was deemed a safe and effective choice as an add-on to risperidone for children with ASD, based on ABC-C irritability subscale 44). Further studies looking at clinical utility of minocycline as a monotherapy or an add-on to risperidone for symptoms of ASD in not only child/adolescent but also adult patients are needed.…”
Section: Immunomodulatory Treatmentmentioning
confidence: 99%
“…A small pilot trial (n=10) with minocycline up to six months showed only minimal improvement, and neither yielded any significant behavioral improvement in ASD nor showed any observable changes in key inflammatory cytokines, such as IL-1β, IL-6, TNF-α, or MMP 43). More lately, however, minocycline was deemed a safe and effective choice as an add-on to risperidone for children with ASD, based on ABC-C irritability subscale 44). Further studies looking at clinical utility of minocycline as a monotherapy or an add-on to risperidone for symptoms of ASD in not only child/adolescent but also adult patients are needed.…”
Section: Immunomodulatory Treatmentmentioning
confidence: 99%
“…Moreover, this antibiotic is known for its antioxidant and anti‐inflammatory characteristics, which could further explain its neuroprotective effects . Previously, we have demonstrated the beneficial role of minocycline in improving symptoms of schizophrenia, depressive and autistic symptoms . The present study was conducted to investigate the efficacy and safety of minocycline as an augmentative agent to fluvoxamine, an SRI strongly supported by OCD randomized trials in treatment of moderate‐to‐severe OCD patients …”
mentioning
confidence: 94%
“…A thorough physical examination was conducted at each visit. Adverse events were systematically recorded at each visit using a checklist (Akhondzadeh, Malek‐Hosseini, Ghoreishi, et al, ; Ghaleiha, Alikhani, Kazemi, et al, ). Necessary lab tests including complete blood count, aspartate aminotransferase, and alanine aminotranferase were checked every month.…”
Section: Methodsmentioning
confidence: 99%